2000
DOI: 10.1128/mcb.20.16.5865-5878.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of c-SRC Activity and Function by the Adapter Protein CAS

Abstract: SRC family kinases play essential roles in a variety of cellular functions, including proliferation, survival, differentiation, and apoptosis. The activities of these kinases are regulated by intramolecular interactions and by heterologous binding partners that modulate the transition between active and inactive structural conformations. p130 CAS (CAS) binds directly to both the SH2 and SH3 domains of c-SRC and therefore has the potential to structurally alter and activate this kinase. In this report, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
147
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 92 publications
12
147
0
Order By: Relevance
“…Second, it has high affinity binding abilities to Src SH2 and SH3 domains, which allows it to bind competitively to c-Src and other Src family members and activate these protein tyrosine kinases. pp125FAK (37) and pp130CAS (38) are also potential Src activators with Src SH2 and SH3 binding motifs. Their distribution is also associated with cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has high affinity binding abilities to Src SH2 and SH3 domains, which allows it to bind competitively to c-Src and other Src family members and activate these protein tyrosine kinases. pp125FAK (37) and pp130CAS (38) are also potential Src activators with Src SH2 and SH3 binding motifs. Their distribution is also associated with cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…SRC was shown to bind to the Src-binding site and to phosphorylate several YXXP motifs of BCAR1 [30][31][32][33]. These experiments have shown that BCAR1 phosphorylation may be important for some processes (cell migration), but not essential for anchorage-independent growth of SRC transformed fibroblasts [7,23,24,[34][35][36].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, overexpression of the CAS C-terminal region including the SBD promoted soft agar colony formation in murine C3H10T1/2 fibroblasts overexpressing c-Src (Burnham et al, 2000). Under these conditions, the interaction of the CAS SBD with the Src SH3 domain appears to relieve c-Src autoinhibitory interactions and thereby stimulate Src kinase activity (Burnham et al, 2000;Pellicena and Miller, 2001), essentially converting c-Src into an activated oncogenic form.…”
Section: Introductionmentioning
confidence: 99%